Estrutura, ultraestrutura e morfometria da aorta de paca (Cuniculus paca, Linnaeus, 1766) criada em cativeiro - Garcia Filho, S. P. [UNESP]; Martins, L. L. [UNESP]; Reis, A. C.G. [UNESP]; Pacheco, M. R. [UNESP]; Machado, M. R.F. [UNESP] (FapUNIFESP (SciELO), 2012)
The aim of this study was to describe the morphology, morphometry and ultrastructure of segments of thoracic and abdominal aorta portions in four male and female paca (Cuniculus paca). Parts of the segments were examined by light microscopy and part by scanning electron microscopy. Thickness measurements of the tunica intima and media complex and tunica adventitia of the aorta were taken. In all animals the thickness values for the tunica intima and media complex of the cranial thoracic aorta were significantly higher (mean: 702.19μm) when compared to the values of other aortic segments analyzed (means: 354.18μm; 243.55μm). The layers of the vessel walls show variations in structure and thickness, presumably due to an adaptation to functionaldemand.
Structure, ultrastructure and morphometry of the aorta in the paca (Cuniculus paca, Linnaeus, 1766) raised in captivity
Keywords: Histology; Hystricomorph; Paca; Rodent; Ultrastructure